Coagulation/ Flocculation, Microfiltration and Nanofiltration for Water Treatment of Main Outfall Drain for Injection in Nasiriyah Oil Field - Faiq Al-Alawy, Ahmed; Jabbar Madlool, Jaafar (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
The present work aims to study the efficiency of coagulation/ flocculation as 1st stage, natural gravity water filter or microfiltration (MF) as 2nd stage and nanofiltration (NF) technology as final stage for treatment of water of main outfall drain (MOD) for injection in Nasiriyah oil field. Effects of operating parameters such as coagulant dosage, speed and time of slow mixing step and settling time in the 1st stage were studied. Also feed turbidity and total suspended solids (TSS) in the 2nd stage were studied. Also feed concentration, temperature and operating time, in the final stage were studied. The results showed that the optimum dosage for alum was 35, 40 and 50 ppm. While, for ferric chloride it was 15, 20 and 30 ppm and for polyelectrolyte 4, 8 and 10 ppm for 11.8, 30 and 100 NTU initial turbidity respectively. The optimum speed for the 2nd step was 25 rpm for each of alum 35 ppm, ferric chloride 15 ppm and polyelectrolyte 4 ppm. While the optimum time for the 2nd step was 30 min for each of alum 35 ppm, ferric chloride 15 ppm and polyelectrolyte 4 ppm and settling time was 30 min for each of alum 35 ppm, ferric chloride 15 ppm and polyelectrolyte 4 ppm. It was found that turbidity and TSS increases by increasing the inlet turbidity and TSS. Also it was found that salts concentration in product increases by increasing feed concentration and temperature. Rejection percentages were (94.475 – 95.631 %), (88.088 – 90.714 %), (83.33 – 93.2 %), (85.116 – 92.727 %) and (65.385 – 72.727 %) for sulphate, total hardness (TH), Ca2+, Mg2+ and Cl- respectively and recovery percentage of product water was (11.429 – 38.143 %) for polyamide membrane (TFC). In the case of concentrate recirculation, feed concentration, permeate concentration and volume of permeate increases with increasing in operating time and 12.69 liter of water valid for injection in oil field was recovered from 25 liter feed after 180 minute.